Ultrasonic Assisted Fused Deposition Modeling For Acrylonitrile Butadiene Styrene Waste Recycling - Ting, Kung Hieng (2021)
Additive manufacturing (AM), also known as 3D printing, is a process that creates a physicalobject from a digital CAD data. Fused Deposition Modeling (FDM) is one of the common 3D printing processes. However, a large amount of waste produced due to printing and human errors. Waste has caused an impact on the environment due to the non-biodegradable polymer properties and this requires recycling of the waste polymers. However, recycled polymers deteriorate in terms of mechanical properties due to weak interlayer bonding. Hence, this study aims to investigate the effect of ultrasonic vibration on the improvement of mechanical properties of recycled Acrylonitrile Butadiene Styrene (ABS). ABS waste was granulated and extruded into a new filament that used to print the test specimen. A piezoelectric transducer mounted onto the FDM printer platform to transmit the vibration thoroughly during the printing of the test specimen. The ultrasonic frequency of the transducer controlled at 0 kHz, 10 kHz and 20 kHz. Specimen orientation controlled at the edge, flat and upright position (X, Y and Z). Tensile test and microstructure analysis carried out to determine the mechanical properties of the recycled ABS specimen at different ultrasonic frequencies and orientation. Analysis of variance (ANOVA) will determine the significant and optimum parameters. The result of the tensile test shows that there had an increment in Ultimate Tensile Strength in the range (UTS) of 11.03% to 67.61%; improvement of strain in the range of 1.30% to 45.83% and improvement of Modulus of Elasticity (MOE) in the range of 15.24% to 24.10%. Besides, the results from the microstructure analysis showed that size voids decreased from 230 µm to 30 µm when the ultrasonic frequency increased to 20 kHz. The results of ANOVA showed that ultrasonic frequency and orientation had a significant effect on the improvement of UTS, strain and MOE and the optimum parameter was 20 kHz of ultrasonic frequency and Y orientation. Hence, this study has shown that ultrasonic vibration can improve the mechanical properties of recycled ABS and reducing the number and size of voids and porosities in its microstructure